The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/2249-4847.134679
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic profile in healthy premature neonates; Does birth weight affect the coagulation profile?

Abstract: Context:There are limited studies assessing the neonatal hemostatic factors in relation to birth weight.Aims:This study aims to compare the coagulation factors between three groups of neonates with different birth weight for gestational age (GA).Settings and Design:In a cross-sectional study, 74 healthy premature neonates were involved.Subjects and Methods:Serum prothrombin time (PT), activated partial thromboplastin time (APTT), international normalized ratio (INR), thrombin clotting time (TT), and levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…However, Perlman and Dvilansky 64 found no difference in levels of factors V and VIII. Plasma concentrations of inhibitors of coagulation, such as protein S and antithrombin, were lower in FGR infants, although one study reported high levels of protein C. 14,71,75 Increased levels of tPA 14,70 and lower plasma fibrinogen were also reported, 13,65,68,70 although these observations were not confirmed in other studies. 64,69 No difference in plasminogen levels is usually noted; 69 however, one paper claimed a decrease in plasminogen levels in IUGR term neonates, especially when complications in the perinatal period occurred.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…However, Perlman and Dvilansky 64 found no difference in levels of factors V and VIII. Plasma concentrations of inhibitors of coagulation, such as protein S and antithrombin, were lower in FGR infants, although one study reported high levels of protein C. 14,71,75 Increased levels of tPA 14,70 and lower plasma fibrinogen were also reported, 13,65,68,70 although these observations were not confirmed in other studies. 64,69 No difference in plasminogen levels is usually noted; 69 however, one paper claimed a decrease in plasminogen levels in IUGR term neonates, especially when complications in the perinatal period occurred.…”
Section: Discussionmentioning
confidence: 92%
“…13 As stated above, liver is one of the first organs affected by chronic hypoxia and as such the production of proteins, such as clotting factors, could be reduced. As for standard coagulation tests, PT, APTT and INR are usually prolonged, 11,14,64,65,68,71 although some studies detected no difference in these parameters in SGA vs AGA infants. 66,72 Among the few studies that investigated vitamin K-dependent coagulation factors II and X, they were not altered by growth restriction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hal ini sejalan dengan penelitian sebelumnya oleh Salonvaara dkk 9 yang mendeteksi penurunan pada faktor V dan faktor VII pada bayi KMK dibandingkan SMK. Abdollahi dkk 19 Salonvaara dkk 9 melaporkan bahwa bayi asfiksia dengan skor APGAR <7 pada menit ke-5 mengalami pemanjangan studi koagulasi berupa faktor II, V, VII, X, dan pemanjangan prothrombin, sedangkan partial thomboplastin time tidak memanjang. Studi lain oleh Murthy dkk 22 melaporkan bahwa bayi dengan asfiksia berat (skor APGAR <7 pada menit ke-5) mengalami pemanjangan PTTK (pemanjangan jika nilai lebih besar dari kontrol).…”
Section: Pembahasanunclassified